Last Kingdom Season 3 Disc 4 - Dreymon, Alexander, 1983-; Dawson, David, 1982-; Cox, Emily, 1985-; Universal Pictures Home Entertainment (Firm) (United States Universal Pictures Home Entertainment, 2018)
Dark forces are moving outside the court and when a powerful Danish warlord Bloodhair attacks, Uhtred must lead Wessex's forces into battle. He captures Bloodhair's mysterious lover, the savage sorceress Skade, who throws a curse and his world becomes blighted by tragedy.
Title from container.
Widescreen (1.78:1)
Alexander Dreymon, David Dawson, Emily Cox, Matthew MacFadyen, Ian Hart.
Rating: Not rated CHV rating: 14A.
DVD; Widescreen (1.78:1) presentation; Region 1, NTSC; Dolby digital 5.1, surround.
Subtitled for the deaf and hard of hearing (SDH).
Keywords: Alfred, -- King of England, -- 849-899 -- Drama; 449-1066; Vikings -- Great Britain -- Drama; Orphans -- Great Britain -- Drama; Orphans -- Drama; Great Britain -- History -- Alfred, 871-899 -- Drama; Great Britain -- History -- Anglo-Saxon period, 449-1066 -- Drama; Drama; Fiction television programs; History; Television series; Video recordings for the hearing impaired